“Apocryphal Acts of the Apostles”: A Problematic Designation - Gounelle, Rémi (Novum Testamentum, 2025)
In this article, the author argues that the history of research on the apocryphal acts of the apostles is still largely influenced by the biblical canon and by the habits of reading and interpretation that are a natural consequence of it. He first shows that the modern habit of designating a varied body of late ancient literature as “apocryphal acts,” opposed to canonical Acts, has obscured the many differences among these texts and overlooked their medieval designations. He then discusses how works categorized as “apocryphal acts” have been closely compared to Acts in biblical research, and shows that it does not correspond to the way these texts were perceived in antiquity and in Byzantium. Last, the author reviews the data showing that the canonical and apocryphal books were not rivals and that the books categorized as “apocryphal acts” were not understood in this way in Church tradition.